Effect of feeding methods of katuk (Sauropus androgynus) extract on performance and carcass quality of broiler chickens - U Santoso; T Suteky; Heryanto .; Sunarti . (Jurnal Ilmu Ternak dan Veteriner, 2002)
The present experiment was conducted to evaluate effect of feeding methods of katuk extract on performance and carcass quality of broilers. Sixty 20-d-old male broilers were distributed to 5 treatment groups of 4 replicates with 3 birds each. One treatment group was fed basal diet without katuk extract (P0), whereas other treatment groups were fed basal diet plus 18 g katuk extract/kg diet (P1), basal diet plus 9 g katuk extract/l drinking water (P2), basal diet plus 9 g katuk extract/kg diet plus 4.5 g katuk extract/l drinking water (P3), and basal diet plus 4.5 g katuk extract/kg diet plus 2.25 g katuk extract/l drinking water (P4). Experimental results showed that weight gain of P1 and P4 were significantly higher (P<0.05) than those of P0 and P2. Feed conversion ratio of P1 and P4 were significantly lower than those of P0 and P2 (P<0.05). Feed intake, water intake, the weights of heart, liver and gizzard were not significantly different (P>0.05), but the weight of intestine was significantly affected (P<0.05) Abdominal fat of P4 was significantly lower than that of P0, P1 and P2 (P<0.05). Carcass color of P4 was significantly better than that of P0, P1, P2 and P3 (P<0.01). Katuk extract feeding had no effect on smell and taste of meat (P>0.05). P4 had better meat color than P0, P1, dan P2 (P<0.05). Katuk extract feeding had no effect on meat bone ratio, carcaas weight and cooking loss (P>0.05). In conclusion, in order to improve performance and carcass quality, broiler chickens could be given katuk extract through diet plus drinking water at level of 4.5 g/kg diet plus 2.25 g/l drinking water.   Key words: Katuk extract, performance, carcass quality, abdominal fat